Lion & Lamb [compact disc, unabridged] - Patterson, James, 1947-; Swierczynski, Duane (Hachette Audio, 2023)
"The city is in a state of shock over the fate of two hometown heroes: Eagles starting quarterback Archie Hughes, and his even more famous wife, Grammy-winning singer Francine Hughes. One spouse is murdered. The other is suspect #1. Even before the case hits the courtroom, it's the hottest ticket in town. For the defense: Cooper Lamb, private investigator to the stars. For the prosecution: Veena Lion, a sleuth so bright she's got to wear shades. Between them, they know every secret in Philadelphia. Together, they prove how two wrongs can make a right. They are Lion & Lamb" --